1982
DOI: 10.1161/01.cir.65.7.1474
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced atrioventricular conduction in patients without preexcitation syndrome: relation to heart rate in paroxysmal reciprocating tachycardia.

Abstract: We studied the electrophysiologic characteristics of atrioventricular (AV) nodal conduction in patients with reciprocating tachycardia (RT) without ventricular preexcitation, and the relation of these characteristics to RT cycle length (CL). Thirty-five symptomatic patients who had a normal PR interval (0.13-0.20 second) during sinus rhythm underwent detailed intracardiac electrophysiologic study during which ventricular preexcitation was excluded, and the RT mechanism was determined. RT was due to reentry usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

1986
1986
2012
2012

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…A 56-year-old doctor developed severe chest pain and had received emergency AC bypass surgery for acute myocardial infarction because of rapidly progressive cardiogenic shock (7). Recovery had been uneventful for 24 hours postoperatively until transient ventricular tachycardia developed.…”
Section: Case Reportmentioning
confidence: 99%
“…A 56-year-old doctor developed severe chest pain and had received emergency AC bypass surgery for acute myocardial infarction because of rapidly progressive cardiogenic shock (7). Recovery had been uneventful for 24 hours postoperatively until transient ventricular tachycardia developed.…”
Section: Case Reportmentioning
confidence: 99%
“…These studies [6][7][8][9] clearly show that the LGL syndrome eponym should be abandoned since the presence of a short PR is not a necessary feature for the tachycardia substrate. Specifically, patients with AV nodal reentry, atrial tachycardia, atrial fibrillation, etc., may suffer from these arrhythmias whether the PR is short or normal.…”
mentioning
confidence: 97%
“…Further studies [6][7][8] emphasized that the AV nodal refractory period was short in these patients and that a small minority of patients would show an essentially flat A-H response with respect to atrial overdrive pacing with an unchanged A-H during programmed atrial extrastimuli. A seminal study was reported by Jackman et al 9 in an invasive electrophysiologic study of 180 patients.…”
mentioning
confidence: 99%